Spatial and temporal population interactions between the parasitoids Cotesia flavipes and Tachinidae flies: considerations on the adverse effects of biological control practice - Rossi, M. N.; Fowler, H. G. (Blackwell Verlag Gmbh, 2004)
Biological control of Diatraea saccharalis is regarded as one of the best examples of successful classical biological control in Brazil. Since the introduction of the exotic parasitoid Cotesia flavipes, the decrease of D. saccharalis infestation in sugarcane fields has been attributed to the effectiveness of this agent. Recently, the native tachinid fly parasitoids (Lydella minense and Paratheresia claripalpis) have also been implicated in the success. Here, we investigated the spatial and temporal population interactions between C. flavipes and the tachinid flies, and provide a critical analysis of the biological control practice, focusing on the undesirable effects of introductions of exotic natural enemies. To investigate these questions, a large data set comprising information from two sugarcane mills located in the state of São Paulo, Brazil (Barra and Sao Joao Mills), was analysed. Analysis of the correlation between C. flavipes and tachinid fly population densities through time revealed that such populations were inversely correlated in the Sao Joao Mill and not correlated in the Barra Mill. Logistic regressions were computed to investigate the proportion of sites occupied by the parasitoid species at both mills as a function of time. An increasing trend in the proportion of sites occupied by C. flavipes was observed, with a concomitant decrease of the sites occupied by tachinid flies. This effect was more intense in the Sao Joao Mill. Thus, there is a convincing possibility that constant releases of C. flavipes decreased the tachinid fly populations, resulting in an undesirable effect of biological control practice.
Keywords: Cotesia flavipes; Diatraea saccharalis; biological control; exotic natural enemies; non-target organisms; spatial scale; Tachinidae